2007
DOI: 10.1016/j.yexcr.2007.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic nanostructures inducing differentiation of human mesenchymal stem cells into neuronal lineage

Abstract: Human mesenchymal stem cells (hMSCs) have been shown to trans-differentiate into neuronal-like cells by culture in neuronal induction media, although the mechanism is not well understood. Topography can also influence cellular responses including enhanced differentiation of progenitor cells. As extracellular matrix (ECM) in vivo comprises topography in the nanoscale, we hypothesize that nanotopography could influence stem cell differentiation into specific non-default pathways, such as transdifferentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
685
6
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 705 publications
(725 citation statements)
references
References 34 publications
30
685
6
4
Order By: Relevance
“…On the titanium nanotubes, tube diameters of 70 and 100 nm enhanced the expression of different osteogenic markers in mesenchymal stem cells compared with cells on a flat titanium surface [21]. On nanogratings, also an up-regulation of neuronal markers, such as microtubule-associated protein 2, was observed in mesenchymal stem cells [22]. This effect of the nanostructure on the neuronal differentiation was stronger than biochemical cues which were added to induce neuronal differentiation.…”
Section: Cell Regulation By Physical Characteristics Of a Materials Tomentioning
confidence: 92%
“…On the titanium nanotubes, tube diameters of 70 and 100 nm enhanced the expression of different osteogenic markers in mesenchymal stem cells compared with cells on a flat titanium surface [21]. On nanogratings, also an up-regulation of neuronal markers, such as microtubule-associated protein 2, was observed in mesenchymal stem cells [22]. This effect of the nanostructure on the neuronal differentiation was stronger than biochemical cues which were added to induce neuronal differentiation.…”
Section: Cell Regulation By Physical Characteristics Of a Materials Tomentioning
confidence: 92%
“…order/disorder. In a different study, Yim et al [83] demonstrated that nanograted substrata were able to induce transdifferentiation of human mesenchymal stem cells (MSCs) in neurons.…”
Section: Topo-cue-mediated Crosstalkmentioning
confidence: 99%
“…It is therefore reasonable to expect that the presentation of topographic signals is one of the strategies that Nature adopts to impart to cells specific orders, which eventually dictate their behaviour. In fact, many works demonstrated that patterned substrates strongly influence cell adhesion, migration and differentiation, suggesting that the presentation of topographic signals might be a powerful tool to control and guide cell behaviour in vitro [4][5][6][7][8]. Indeed, recent literature has addressed the importance of the material-cytoskeleton crosstalk, which is at the helm of the biophysical and biochemical stimuli eventually governing cell fate and functions [9].…”
Section: Introductionmentioning
confidence: 99%